2018
DOI: 10.14295/cs.v9i2.2734
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and elementary characterization of humic substances in organic substrates

Abstract: The humic substances, major constituents of the organic matter of the substrates, play an important role in plant development, including: the availability of nutrients, the generation of negative charges (CEC) and the buffering effect. Based on this, this study aimed to use the molecular absorption spectroscopy in the ultraviolet-visible region (UV-VIS), the vibrational spectroscopy Fourier transform infrared (FTIR) and the elementary analysis CHN/O techniques to characterize the humic acid (HA) and fulvic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Comparing both methods used here, UV-VIS spectroscopy is useful in determining the absorbance of aromatic systems, which is related to the degree of humic substances' humification as well as the quality of soil (Da Silva et al 2018), whereas the ADI showed the diversity of the degree of organic matter stabilization. The ADI correlated with organic carbon content and is especially dependent on soil colour and the amount of material scattered as well as its exposure time (Mazurek et al 2016).…”
Section: A Horizon Development Index and Uv-vis Spectroscopic Coeffic...mentioning
confidence: 99%
“…Comparing both methods used here, UV-VIS spectroscopy is useful in determining the absorbance of aromatic systems, which is related to the degree of humic substances' humification as well as the quality of soil (Da Silva et al 2018), whereas the ADI showed the diversity of the degree of organic matter stabilization. The ADI correlated with organic carbon content and is especially dependent on soil colour and the amount of material scattered as well as its exposure time (Mazurek et al 2016).…”
Section: A Horizon Development Index and Uv-vis Spectroscopic Coeffic...mentioning
confidence: 99%
“…FAs isolated from various soils differed significantly in terms of chemical and structural properties ( Table 1). The H/C atomic ratio showed the highest value for FA2 (0.94) while indicating the lowest degree of condensation of aromatic rings, and thus the greatest proportion of aliphatic structures in relation to FA3, which showed the lowest H/C value (0.85) [13,37]. The highest O/C and O/H ratios were determined for FA2 sample, while the lowest ones for FA3, which indicated a higher content of oxygen structures and as a higher humification degree of FA2 as compared to FA3.…”
Section: Fulvic Acidsmentioning
confidence: 99%
“…Some exemplary FTIR characteristics are shown in Figure 5 (black, solid lines). Some of the observed signals can be considered important in terms of interaction with Zn(II): (a) wide intensive band at 3435 cm −1 attributed to the N-H stretch of amines and O-H of hydroxyl groups in hydrogen bonds, carboxylic acids, alcohols and phenols [5,13,16], (b) vibrations at~1710 cm −1 related to C=O stretching of protonated carboxyls, quinines, cyclic and acyclic aldehydes and ketones [42,68], (c) band at~1625 cm −1 refers to C=O bonds of deprotonated COO-, C-O and C-N stretching in amides [13,69] as well as vibrations of -C = C-on benzene rings [16,42], (d) peak at~1400 cm −1 reflecting aliphatic -C-H deformation, -COO-symmetric stretching and -O-H deformation [5], (e) vibrations at~1220 cm −1 corresponded to C-O stretching in phenols, carboxylic acids and ethers [68,70] and (f) band at~1070 cm −1 , indicating the presence of polysaccharides, ethers and alcohols attributed to the stretches of C-O bond [5,13]. The increase of pH caused a gradual reduction of the bands at~1710 cm −1 and at~1220 cm −1 and enhancement of the bands at~1625 and at~1400 cm −1 , which was associated with the successive deprotonation of surface COOH groups and, consequently, an increase of the COO − fraction.…”
Section: Ftir Spectra Of Fa-zn(ii) Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the present study, it was 0.65%. High O/C ratio observed presently suggested that the humic substances have undergone a low degree of condensation and are more aliphatic in nature with a higher proportion of carbohydrates (Mengchang et al 2008;Guéguen et al 2012;da silva et al 2018).…”
Section: Elemental Analysismentioning
confidence: 99%